Interspecific associations of mangrove species and their preferences for edaphic factors and water quality (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Marpaung BA, Budiadi, Pertiwiningrum A, Lestari LD, Nurjanto HH, Widiyatno. 2022. Interspecific associations of mangrove species and their preferences for edaphic factors and water quality. Biodiversitas 23: 4626-4635. Scientists from different regions have reported failures of mangrove restorations that were predicted due to the unsuitability of the species for the habitats. Habitat preferences should become an important consideration for mangrove restoration and management. This study aimed to find interspecific associations between species and examine the edaphic factors and water quality suitable for mangroves. Eight research stations (and 24 sample plots) were established purposively based on the vegetation structure and salinity levels in successful mangrove restorations in East Lampung in 2020. In each plot, vegetal data and sediment and water samples were taken. The species domination was analyzed using the important value index (IVI), and interspecific associations were determined using a 2x2 contingency table. The edaphic factors and water quality were analyzed using principal component analysis (PCA) to find factors that had significant correlations among others. The effects of the edaphic factors and water quality on species regeneration were analyzed using multiple linear regression by backward elimination to develop a model of habitat preferences for mangroves. Based on the results, Avicennia marina and Rhizophora sp. were the dominant species in all the zones. Still, the lack of interspecific association ( ) showed that both species had different preferences for the habitat. We found four principal components (PCs) of edaphic factors—i.e., the environmental (soil and surface) temperature, dusty clay and Ca, inorganic nitrogen (NH4-N and NO3-N), and Mg—and two PCs of water quality, i.e., nontoxic pollutants (total suspended solids and turbidity) and anthropogenic factors (NO2-N and PO4-P), as predictors for multiple linear regression. The seedlings of A. marina had no specific preferences for edaphic factors but significantly preferred nontoxic pollutants (R2 = 0.619), while the seedlings of Rhizophora spp. significantly preferred a specific environmental temperature, dusty clay and Ca, and inorganic nitrogen (R2 = 0.768), and nontoxic pollutants (R2 = 0.755). Combining A. marina and Rhizophora spp. in mangrove restorations should be avoided. Therefore, spatial planting patterns or sequential planting based on the succession stages of the habitat could be established.